THE INFLUENCE OF POSTPARTUM EXERCISE ON LEVEL OF AFTERPAINS IN POSTPARTUM WOMEN - Anita Lufianti; Masrinia Fatimah; Mika Agustiana (Universitas Karya Husada Semarang, 2025)
Introduction: Postpartum period is the period after childbirth up to 6 weeks or 42 days, during the postpartum period, the reproductive organs slowly undergo changes, namely uterine involution, which can cause post-partum pain. Postpartum exercise is a form of early ambulation for postpartum women aimed at facilitating the involution process. Objective: The purpose of the research is to investigate the influence of postpartum exercise on the level of afterpains. Method: This research using the 'quasi-experimental' method, with a one-group pretest-posttest-design approach. The sample used in this study was 10 respondents at the Permata Bunda Hospital. The sample were taken by purposive sampling The collecting data tool used a standard of operational procedure chcek list of post-partum exercise and observation sheet on pain. Data analysis using paired samples t-test. Result: The result showed the majority of post-partum mother’s pain decreased from moderate pain to mild pain 8 (80%), from severe pain to moderate pain 2 (20 %). There is an effect of postpartum exercises on the level of afterpains in postpartum women p-value of 0.00> 0.05. Conclusion: The results of the respondent's pain level after being given postpartum exercise during the posttest the pain level decreased.